Clinical Efficacy of Transcutaneous Electrical Nerve Stimulation (TENS) in Pediatric Functional Constipation: Impact on Immunological Indicators and Gut Microbiota - Piao Guo; Xue Ning Zhang; Xin Yu Jin; Wen Juan Xia; Li Zhou; Wei Song Sheng; Dan Rong Zhu (Journal of Immunology Research)
Trial Registration: Clinical Trial Registry identifier: ChiCTR2200059549